2015
DOI: 10.1016/j.cbpa.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol affects metabolic and ionoregulatory responses to a different extent depending on feeding ration in common carp, Cyprinus carpio

Abstract: Interacting effects of feeding and stress on corticoid responses in fish were investigated in common carp fed 3.0% or 0.5% body mass (BM) which received no implant, a sham or a cortisol implant (250 mg/kg BM) throughout a 168 hour post-implant period (168 h-PI). At 12h-PI, cortisol implants elevated plasma cortisol, glucose and lactate. Plasma osmolality and ions remained stable, but cortisol increased gill and kidney Na(+)/K(+) ATPase (NKA) and H(+) ATPase activities. Gill NKA activities were higher at 3%-BM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…Serum cortisol and GLU content are considered to be important indicators of stress response in fish (Fanouraki, Mylonas, Papandroulakis, & Pavlidis, 2011;Liew, Fazio, Faggio, Blust, & Boeck, 2015;Wedemeyer, 1976). In the current study, cortisol and GLU content increased in each experimental group when the water temperature decreased from 15 to 10 C. These results are in agreement with those of previous studies on tilapia (Qiang, Yang, Wang, Xu, & He, 2012) and puffer fish, Takifugu obscurus (Cheng, Ye, Guo, & Wang, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum cortisol and GLU content are considered to be important indicators of stress response in fish (Fanouraki, Mylonas, Papandroulakis, & Pavlidis, 2011;Liew, Fazio, Faggio, Blust, & Boeck, 2015;Wedemeyer, 1976). In the current study, cortisol and GLU content increased in each experimental group when the water temperature decreased from 15 to 10 C. These results are in agreement with those of previous studies on tilapia (Qiang, Yang, Wang, Xu, & He, 2012) and puffer fish, Takifugu obscurus (Cheng, Ye, Guo, & Wang, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Serum cortisol and GLU content are considered to be important indicators of stress response in fish (Fanouraki, Mylonas, Papandroulakis, & Pavlidis, ; Liew, Fazio, Faggio, Blust, & Boeck, ; Wedemeyer, ). In the current study, cortisol and GLU content increased in each experimental group when the water temperature decreased from 15 to 10°C.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cortisol is one of the most used indicators to evaluate stress in fish (Wendelaar Bonga, 1997) and the two major actions of this hormone are the control of the ionoregulatory balance and energy metabolism (Liew et al, 2015). The electrolytic imbalance can be observed by changes in plasma or blood ions (McDonald, Milligan, 1997;Wendelaar Bonga, 1997;Takahashi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sarma et al (2011) reported accumulation of ions in the vital organs of Channa punctatus exposed to pesticide, once the gills and kidneys represent the main organs responsible for osmotic regulation in freshwater fish. In addition, the feeding also plays an important role in ionoregulation and in other blood parameters of the fish (Liew et al 2015).…”
Section: Discussionmentioning
confidence: 99%